Perencanaan Bahan Baku OM-Chips Untuk Produk Film G2 Menggunakan Metode Peramalan Dan Metode EOQ - Efendi, Murzid; Juhara, Sutresna; Khamaludin, Khamaludin (UNISTEK, 2022)
PT. INDONESIA TOYOBO FILM SOLUTIONS is an industry that produces plastic sheet / PET film. In this company, there is an accumulation of OM-Chips type of raw material for G2 Film products. The research will apply the Moving Average and Exponential Smoothing Forecasting Methods, and for the planning of the raw materials using the Economic Order Quantity Method. Is this EOQ method capable of costing the raw material inventory so that it can minimize the cost of raw material inventory and the results can also be known later. For forecasting, the results show that the 2-month Moving Average forecasting method has a value of MAD = 19.5 and MAPE = 13.58. For the company's inventory costs in the period August 2020-July 2021 without using the EOQ method, which is Rp. 45,499,623. And after using the EOQ method in the period August 2020-July 2021, the results of the inventory cost of Rp. 36,252,000. There was a decrease in inventory costs in the period August 2020-July 2021 by 11.31%. Meanwhile, the raw material inventory for the upcoming period August 2021-July 2022 uses the EOQ method for the number of economical purchases per order, which is 93.81 Tons, with a purchase frequency of 19 times. And for the safety stock of 41.44 tons with a Re-Order Point value of 246.78. From the results of these calculations, it was obtained that the inventory costs for the August 2021-July 2022 period were Rp. 28,141,500